Una posición intermedia entre el fisicalismo y el intencionalismo: Dennett - Salma Saab (Crítica)
This article assesses Dennett’s position with respect to mental states, intermediate between the extremes of physicalism and intentionalism. Dennett concentrates most of his theses with respect to our atribution of mental states to others, or to other systems, on what he calls the intentional stance. One of his main claims is that, ontologically speaking, mental states as such do not exist but that nevertheless they do have some sort of reality. The elimination of mental entities as “abstracta”. These “abstracta” play an important role in our explanation of what people do and of the way in which certain systems are designed.